Covalent Organic Frameworks for CO2 Capture - Zeng, Yongfei; Zou, Ruqiang; Zhao, Yanli (Advanced materials (Weinheim), 2016)
As an emerging class of porous crystalline materials, covalent organic frameworks (COFs) are excellent candidates for various applications. In particular, they can serve as ideal platforms for capturing CO2 to mitigate the dilemma caused by the greenhouse effect. Recent research achievements using COFs for CO2 capture are highlighted. A background overview is provided, consisting of a brief statement on the current CO2 issue, a summary of representative materials utilized for CO2 capture, and an introduction to COFs. Research progresses on: i) experimental CO2 capture using different COFs synthesized based on different covalent bond formations, and ii) computational simulation results of such porous materials on CO2 capture are summarized. Based on these experimental and theoretical studies, careful analyses and discussions in terms of the COF stability, low‐ and high‐pressure CO2 uptake, CO2 selectivity, breakthrough performance, and CO2 capture conditions are provided. Finally, a perspective and conclusion section of COFs for CO2 capture is presented. Recent advancements in the field are highlighted and the strategies and principals involved are discussed. Covalent organic frameworks (COFs) are excellent candidates for various important applications. Recent research progress on: i) experimental CO2 capture of different COFs according to the covalent bonds formed during the synthetic procedure, and ii) theoretical calculations of CO2 capture by COFs is highlighted. Analyses and discussions based on experimental and theoretical results are also provided.